Economic consequences of high public debt: Evidence from three large scale DSGE models - Pablo Burriel; Cristina Checherita-Westphal; Pascal Jacquinot; Matthias Schön; Nikolai Stähler (European Central Bank (ECB), 2020)
The paper reviews the economic risks associated with regimes of high public debt through DSGE model simulations. The large public debt build-up following the 2009 global financial and economic crisis acted as a shock absorber for output, while in the recent and more severe COVID19-crisis, an increase in public debt is even more justified given the nature of the crisis. Yet, once the crisis is over and the recovery firmly sets in, keeping debt at high levels over the medium term is a source of vulnerability in itself. Moreover, in the euro area, where monetary policy focuses on the area-wide aggregate, countries with high levels of indebtedness are poorly equipped to withstand future asymmetric shocks. Using three large scale DSGE models, the simulation results suggest that high-debt economies (1) can lose more output in a crisis, (2) may spend more time at the zero-lower bound, (3) are more heavily affected by spillover effects, (4) face a crowding out of private debt in the short and long run, (5) have less scope for counter-cyclical fiscal policy and (6) are adversely affected in terms of potential (long-term) output, with a significant impairment in case of large sovereign risk premia reaction and use of most distortionary type of taxation to finance the additional debt burden in the future. Going forward, reforms at national level, together with currently planned reforms at the EU level, need to be timely implemented to ensure both risk reduction and risk sharing and to enable high debt economies address their vulnerabilities.
Keywords: E62; H63; O40; E43; 330; government debt; interest rates; economic growth; fiscal sustainability